Overview of Anxiety Levels of Hemodialysis Patients at Santa Elisabeth Hospital Medan 2022 - Indra Hizkia P; Sry Rumondang Sitindaon; Ervina Saro Butar-butar (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Hemodialysis is a therapy that functions as a kidney replacement. Therefore, good knowledge about hemodialysis is needed to prevent fatal events for health. As a result of this hemodialysis which can cause patients undergoing therapy susceptible to experiencing anxiety. Anxiety is a response to worry that a person gives and feels when he feels threatened and is a very normal thing in life. The literature on the incidence of depression and anxiety in the population is much larger than that found in patients with kidney disease. Data on the prevalence of depression in Indonesia is 6.1‰ and the prevalence of mental emotional disorders (anxiety) is 9.8%. The purpose of the study was to determine the level of anxiety of hemodialysis patients at Santa Elisabeth Hospital Medan in 2022. The study used a descriptive method with sampling using purposive sampling technique, totaling 36 respondents. Data analysis used univariate analysis and the results showed that the anxiety level of hemodialysis patients had a